Comparison of Women’s Labor Market Participation between Types of Childcare Policies Based on Policy Tool Mix - Lee, Chae Jeong; Seo, Inseok; Lee, Youhyun (Journal of Comparative Policy Analysis: Research and Practice, 2023)
This study examines the effect of state-centered childcare policies on women’s labor market participation. It applies the fuzzy-set qualitative method to OECD member countries and classifies countries into seven types based on the mix of childcare policy tools in terms of the state’s directness of funding, directness of service creation, and coerciveness of service quality regulation. This helped identify an effective combination of childcare policy tools for increasing women’s labor market participation. Thus, providing childcare services that policy consumers can trust by increasing the government’s enforcement of qualitative regulations on childcare services is critical.
Keywords: childcare; defamilization; fuzzy-set qualitative comparative analysis (fs-QCA); policy mix; policy tools; women’s labor market participation